PETROGENESIS OF THE META-TRONDHJEMITES FROM CAPE HINODE, EAST ANTARCTICA - イケダ, ヤスオ; シライシ, カズユキ; ヤナイ, ケイゾウ; IKEDA, Yasuo; SHIRAISHI, Kazuyuki; YANAI, Keizo (National Institute of Polar Research, 1997)
P(論文) Meta-trondhjemites (ca. 1000 Ma) from Cape Hinode, Lutzow-Holm Complex (LHC), East Antarctica are characterized by relatively high Al (Al_2O_3>15% at 70% SiO_2) and Sr, and low Y and Yb contents, which are chemically similar to Archaean trondhjemites and adakites. Trace element modelings of the partial melting of MORB suggest that igneous protoliths of the meta-trondhjemites were derived by partial melting of a basaltic source material under garnet stability P-T conditions. We suggest that a young hot subducting plate along LHC at 1000 Ma may have reached elevated temperatures which initiated melting of the slab. departmental bulletin paper